Stress relaxation via addition-fragmentation chain transfer in a thiol-ene photopolymerization - Kloxin, Christopher J. (2009)
Allyl sulfide addition-fragmentation chain transfer was employed concurrently with the radical-mediated formation of a thiol-ene network to enable network adaptation and mitigation of polymerization-induced shrinkage stress. This result represents the first demonstration of simultaneous polymerization and network adaptation in covalently crosslinked networks with significant implications for the fabrication of low stress polymer networks. For comparison, analogous networks incorporating propyl sulfide moieties, incapable of addition-fragmentation, were synthesized and evaluated in parallel. At the highest irradiation intensity, the allyl sulfide-containing material demonstrated a more than 75% reduction in the final stress when compared with the propyl sulfide-containing material. Analysis of the conversion evolution revealed that allyl sulfide addition-fragmentation decreased the polymerization rate owing to thiyl radical sequestration. Slow consumption of the allyl sulfide functional group suggests that intramolecular homolytic substitution occurs by a step-wise, rather than concerted, mechanism. Simultaneous stress and conversion measurements demonstrated that the initial stress evolution was identical for both the allyl and propyl sulfide-containing materials but diverged after gelation. While addition-fragmentation chain transfer was found to occur throughout the polymerization, its effect on the stress evolution was concentrated towards the end of polymerization when network rearrangement becomes the dominant mechanism for stress relaxation. Even after the polymerization reaction was completed, the polymerization-induced shrinkage stress in the allyl sulfide-containing material continued to decrease, exhibiting a maximum in the stress evolution and demonstrating the potential for continuing, longer term stress relaxation.